Perspective: an optoelectronic future for heterogeneous, dendritic computing - El Srouji, Luis; Abdelghany, Mahmoud; Ambethkar, Hari Rakul; Lee, Yun-Jhu; Berkay On, Mehmet; Yoo, S. J. Ben (Frontiers in Neuroscience, 2024)
With the increasing number of applications reliant on large neural network models, the pursuit of more suitable computing architectures is becoming increasingly relevant. Progress towards co-integrated silicon photonic and CMOS circuits provides new opportunities for computing architectures with high bandwidth optical networks and high-speed computing. In this paper, we discuss trends in neuromorphic computing architecture and outline an optoelectronic future for heterogeneous, dendritic neuromorphic computing.